On the mechanism of stimulation by low-concentration stressors in barley seedlings - Kovács, Erika; Nyitrai, Péter; Keresztes, Áron (Acta Biologica Szegediensis, 2008)
Beneficial effect of low-concentration chemical stressors like Cd salt and a herbicide DCMU have been investigated previously in different plant model systems. The symptoms of stimulation are known from earlier studies, but information about the mechanism is limited. In this work, the mechanism of stimulation of low-concentration Cd (5.10-8 M) and 3-(3,4-di-chlorophenyl)-1,1-dimethylurea (DCMU, 10-7 M) was investigated in barley seedlings. In treated plants, the amount of cytokinins increased in roots and, after being transported to the leaves, they caused stimulation of chlorophyll accumulation, photosynthetic activity, and delayed senescence. To identify the signal transduction pathway(s) involved in the primary stimulation of cytokinin synthesis in roots, specific phosphatidylinositol-4,5-bisphosphate – inositol-1,4,5-tri-phosphate/diacylglycerol (PIP2-IP3/DAG) and mitogen activated protein kinase (MAPK) signaling pathway inhibitors were added to the nutrient solutions. Both of them proved to be effective, eliminating the stimulation of the stressors.